Geographic Atrophy Phenotypes in Subjects of Different Ethnicity: Asia-Pacific Ocular Imaging Society Work Group Report 3 - Teo, Kelvin Y C; Fujimoto, Satoko; Sadda, Srinivas R; Kokame, Gregg; Gomi, Fumi; Kim, Judy E; Cheng, Mark F S; Corradetti, Giulia; Amornpetchsathaporn, Anyarak; Chainakul, Methaphon; Lee, Won Ki; Lai, Timothy Y Y; et al. (Ophthalmology retina, 2023)
To characterize geographic atrophy (GA) and evaluate differences between Asians and non-Asians. Multicenter, retrospective case series. Subjects aged ≥ 50 years with GA secondary to age-related macular degeneration in the absence of neovascularization in the study eye and follow-up of ≥ 2 years. The GA lesion characterized at baseline and last follow-up based on multimodal imaging (fundus autofluorescence [FAF], near infrared [NIR], and spectral domain-OCT). Patients were grouped as either Asian or non-Asian. Comparison of (1) phenotypes of GA lesions (size, foveal involvement, number of foci, drusen background, and choroid background) and (2) growth rates of GA. A total of 144 patients (169 eyes) with distribution of 50.9% Asians and 49.1% non-Asians. The age and sex were similar between Asians and non-Asians (Asians: mean age, 77.2 ± 10.1 years, 47.9% female; non-Asians: mean age, 79.7 ± 8.4 years, 58.7% female). Asians exhibited thicker choroids (167 ± 74 versus [vs.] 134 ± 56 μm; P < 0.01) and lower prevalence of drusen (40.7% vs. 66.3%; P < 0.01). At baseline, the GA area was smaller in Asians vs. non-Asians (NIR, 3.7 ± 4.6 vs. 6.3 ± 6.8 mm ; P = 0.01: FAF, 2.4 ± 3.4 vs. 8.4 ± 9.6 mm ; P < 0.01). Asians had fewer GA foci (1.7 ± 1.3 vs. 2.7 ± 2.2; P < 0.01) compared to non-Asians. The proportion with diffused or banded FAF junctional zone pattern was similar between Asians and non-Asians (44.2% vs. 60.2%; P = 0.20). Asians had a slower GA lesion growth rate than non-Asians (NIR, 0.7 vs. 1.9 mm /year; P < 0.01: FAF, 0.3 vs. 2.0 mm /year; P < 0.01: NIR, 0.2 vs. 0.4 mm/year; P < 0.01 square root transformed: FAF, 0.1 vs. 0.3 mm/year; P < 0.01 square root transformed). The factors associated with GA lesion growth rate are (from the highest effect size) ethnicity, junctional zone FAF pattern, baseline GA area, and number of GA foci. Higher GA lesion growth rate was observed in both Asian and non-Asian subgroups, with drusen or lesion size and FAF patterns meeting inclusion criteria of recent therapeutic trials, but growth rate remained significantly slower in Asians. Eyes with baseline lesion ≥ 5 mm showed the highest growth rate, and the difference between ethnicities was no longer significant (2.6 vs. 3.3 mm /year; P = 0.14). There are differences in GA lesion phenotype, associated features, and growth rate between Asians and non-Asian subjects. Proprietary or commercial disclosure may be found after the references.